Hydrogels with Tunable Physical Cues and Their Emerging Roles in Studies of Cellular Mechanotransduction. Issue 10 (11th July 2021) - Narasimhan, Badri Narayanan; Horrocks, Matthew S.; Malmström, Jenny
Abstract : The extracellular matrix provides complex biophysical cues to cells which respond to these signals with signaling cascades that determine various cellular processes including fate. Many material systems have been explored to mimic the mechanical properties of the extracellular matrix to determine the cell responses to mechanical cues. While stiffness has emerged as an important regulator of cell behavior, recently, other mechanical properties such as strain stiffening and viscoelasticity have also emerged as potent regulators. This review explores the substrates used for studying mechanotransduction and strategies adopted to impart more complex mechanical cues including spatiotemporal control of mechanical properties. In addition, practical considerations for designing hydrogels for cell culture are discussed and the response of cells to viscoelastic cues in particular is discussed in depth. Recent mechanotransduction studies of combinations of mechanical and other cues are finally reviewed. It is anticipated that such multiphysical cues will further the understanding of mechanotransduction involved in complex processes such as migration and mechanical memory and provide a framework in controlling cell behavior. Abstract : The extracellular matrix (ECM) provides various biophysical cues and dictates cellular processes including cell fate. This review explores the ECM mimetic substrates used for providing various mechanical cues for studying mechanotransduction. Specific emphasis is laid on viscoelasticity and also strategies adopted to impart more complex mechanical cues including spatiotemporal control of mechanical properties.